Implikasi Hukum Perubahan Struktur Yayasan Akibat Ketua Pembina Meninggal Dunia : Analisis Yuridis terhadap Putusan No. 3295 K/PDT/2024 - Suprayitno; Sarah Rosanna Anwar; HASIM PURBA (Jurnal Hukum Lex Generalis, 2026)
The death of the Chairperson of the Foundation’s Board of Trustees creates legal issues regarding the filling of vacant positions when the remaining Trustee does not attend meetings without formally resigning. This normative juridical research analyzes the authority of a sole Trustee, the validity of meetings conducted without a quorum, and Supreme Court Decision Number 3295 K/Pdt/2024. The study finds that a sole Trustee is authorized to appoint the Management Board and the Supervisory Board but is not authorized to appoint new Trustees. Meetings held without a quorum are considered invalid as long as other Trustees remain active, and the Supreme Court annulled the changes to the foundation’s organizational structure by applying a formalistic approach.